PREVENTION OF COMPUTER CRIME THROUGH KNOWLEDGE OF THE CONCEPT OF CYBER SECURITY - POP, Ionuț– Andrei (International Journal of Legal and Social Order, 2022)
The purpose of this article is to make the reader aware of the concept of cyber security and of the importance of establishing cyber data protection systems that we currently manage. Cyber-attacks have experienced a continuous upward trend in recent years, being targeted at both personal computer systems, computer systems managed by companies or computer systems managed by state institutions, as such cyber security has become a necessity for any user, provider, or consumer of cyber data.